The degradation of skill?: understanding the acquisition, development and maintenance of 'skills' in the context of South African capitalism - Tshabalala, Themba (My University, 2018)
This research project has attempted to understand and articulate the relationship between ‘capitalist deskilling’ and the post-apartheid discourse of skills development. It has engaged the contradiction that seems to exist in the current ‘skills’ discourse, using a labour process approach. Put briefly, if all capitalist societies inevitably degrade skilled-labour for the purpose of increasing surplus-value, why is South Africa, as a capitalist society, constantly lamenting the lack of skills? What does it mean for management to complain about not having skills, if having them may mean fewer profits? Why, for the past three decades to date have there been concerted efforts, from government, industry and education to produce skilled-labour if skilled-labour has the potential of demanding higher wages? Using the ideas of Braverman (1974) on the capitalist labour process and its effects on skilled-labour as an entering-wedge, the findings from this project have articulated the state of ‘skills’ in democratic South Africa. Chisholm (1983) has argued that most of the discourse (and ensuing practise) that has arisen from the drive to revive skilled labour in South Africa was characterised by what she refers to as ‘technicist’ interpretations to explaining and dealing with the skills-impasse. These (in our generation) are typically initiatives to improve the education system for the training of skilled labour and create synergy between society, education, industry and government. These are ‘technicist’ because they focus on the ‘technical’ aspects of the skills impasse. They emphasize that the problem of skills is simply a technical discrepancy, that if pedagogy, transition-into-the-workplace strategies, labour and educational policies around skills are improved, this will lead to the eradication of the problem with all its ramifications. These approaches do not consider what the ideological and social dimensions of the skills-impasse may be and hence this predicament may plague South African society for a long time to come. Choosing skilled labour from the apparel sector as a case, this project has sought to provide a socio-ideological approach towards articulating the state of skills in South Africa. I argue that the discourse of ‘skills’ is a governmental strategy used by the South African capitalist state to rationalize the risks of free-market capitalism, to further segment the working classes and to transfer the responsibility of a lack of adequate social protection to the masses. The framework for this project is qualitative; the strategy is a case study with ‘ethnographies of work’ of respondents from the Johannesburg apparel sector. Open-ended interviews were used to collect data and discourse analysis was used to argue that the ‘skills-debate’ is a discourse in and of itself.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Development Studies, School of Social Sciences, Faculty of Humanities, University of the Witwatersrand, April 2018
Keywords: Post-apartheid era--South Africa; Democracy